Peran Self-Directed Learning dan Kecerdasan Buatan (AI) dalam Meningkatkan Motivasi Belajar Mahasiswa: The Role of Self-Directed Learning and Artificial Intelligence (AI) in Improving Student Motivation to Learn - Fatah, Aldinova Noor; Gumilar, Rendra; Sartika, Sri Hardianti (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to examine the effect of self-directed learning and the use of artificial intelligence (AI) in learning on the learning motivation of Economics Education students at Siliwangi University. A quantitative approach was used in this study with a survey method through distributing questionnaires to 221 students selected using the Proportional Stratified Sampling technique. The results showed that self-directed learning has a positive and significant effect on student learning motivation, with a tcount value of 8.411 and a significance of 0.000 (p < 0.05). The use of AI in learning also has a significant positive effect, with a tcount value of 2.327 and a significance of 0.021 (p < 0.05). The coefficient of determination (R²) of 0.382 indicates that these two independent variables explain 38.2% of the variation in learning motivation, while the rest is influenced by other factors outside the research model. This finding confirms that the combination of self-directed learning and AI utilization can be an effective strategy in increasing students' learning motivation and supporting more innovative and independent learning.